A Forced March for Failing Schools: Lessons from the New York City Chancellor’s District. - Phenix, Deinya; Siegel, Dorothy; Zaltsman, Ariel; Fruchter, Norm (Education Policy Analysis Archives, 2005)
In the mid-nineties, the New York City Schools Chancellor created a citywide improvement zone to take over a significant proportion of the city's lowest performing schools whose local community school districts had failed to improve them. This "Chancellor's District" defined centralized management, rather than local control, as the critical variable necessary to initiate, enforce and ensure the implementation of school improvement. This large-scale intervention involved both a governance change and a set of capacity-building interventions presumably unavailable under local sub-district control. Our study retrospectively examined the origins, structure and components of the Chancellor's District, and analyzed the characteristics and outcomes of the elementary schools mandated to receive these interventions. Our longitudinal analysis compared Chancellor's District schools to New York City's other state-identified low performing schools, based on a school-level panel of performance, demographic, human resource, and expenditure data collected from district Annual School Report Cards and School Based Expenditure Reports from 1998-99 through 2001-02. The results suggest that the Chancellor's District intervention improved these schools' instructional capacity and academic outcomes, both relative to where these schools would have been and relative to comparable schools.